Subclass of Multivalent β-Uniformly Functions with Varying Arguments. (8th January 2013) - El-Ashwah, R. M.; Aouf, M. K.; Hassan, A. A. M.; Hassan, A. H.
Abstract : We introduce a class of multivalent β -uniformly functions with varying arguments, give some properties of functions in this class, and obtain sharp results including coefficient estimates and distortion theorems. Finally, we give the extreme points for this class.